Spirituality of lengger dance in papringan hamlet Banyumasan - Heni Siswantari; Lovandri Dwanda Putra; Ganing Rimas Hayu Kerti (International Journal of Visual and Performing Arts, 2022)
Lengger dance, as one of the local wisdom of the Banyumas community, is considered by the wider community to have no Islamic values. However, the fact is that every art that grew from the people of the archipelago emerged for reasons of spirituality, getting closer to God and nature so that when Islam was present in the archipelago, Islamic values were very easily integrated into these arts. This research aims to examine more deeply and describe the value of spirituality in the Banyumas Lengger dance. The research method used in this study is qualitative with an ethnographic approach. The subject of this research is the Lengger Banyumasan art, and the paradigm used is spirituality and Islamic values in the process, movement, and accompaniment of the Banyumasan Lengger dance. Data regarding dance movements were obtained through the process of observing and interviewing the dancers. Furthermore, the research explored whether religious values were taken into consideration in creating the musical accompaniment for the Lengger dance performances. The results showed that the Banyumasan lengger dance contained spiritual values related to God, fellow human beings, and the environment. The spiritual values found in the lengger dance in Papringan Hamlet, Banyumas is the local community's belief in the existence of indhang, offerings offered to the indhang, movements that are considered erotic have spiritual value and gratitude to the power, and there are several taboos for lengger dancers